"É hip hop na minha embolada": o salto espetacular do break ao mangue dos jovens Chico Vulgo e Jorge dü Peixe – Recife, 1984-1994 - Nascimento, Francisco Gerardo Cavalcante do (2019)
The thesis seeks to show that the MangueBit movement was set up as a counter-spectacle in Recife in the mid-1980s and early 1990s. Its guiding thread is directed towards the artistic steps of young Chico Vulgo (or Science) and Jorge dü Peixe in the period for us considered as pre-MangueBit, at a time when the city of Recife was experiencing a deep social and economic crisis, to the point that Population Crisis Committee, based in Washington (USA), registered it as one of the worst cities to live in the world. The capital of Pernambuco offered little life prospects to its poorest inhabitants, especially for the youth in suburbs. The dance gang Legião Hip Hop from Rio Doce neighborhood in Olinda, and the groups formed in the following years (Orla Orbe, Bom Tom Rádio, Loustal, Chico Science and Lamento Negro) served as a script and were essencial to chart the way followed by a portion of these young people who developed a notion of belonging and spatial and social reconfiguration with Recife. For this work, the conceptions derived from cultural and affective cartography supported our idea that music was responsible for the way Chico Vulgo and Jorge dü Peixe went from suburbs to downtown, not as supporters or cheap labor force, but as protagonists of their own stories. In the midst of this analysis, we explored elements that represented, from our point of view, counter- spectacle cultural scenes shown, for example, in clothing revealed as something alive, bearing a singular symbolic charge, associated it with Helio Oiticica’s parangolés. As the apex of the counter-spectacle, we turn to the examination of the contradictions between the secular and the contemporary, between the traditional and the international, conflicts dealt by MangueBit as something positive for the movement support, spread and consolidation, that places face to face the oficial Recife and the real Recife of mocambos, maracatus and break.